Clinical Significance of PIK3CA Gene in Non-Small-Cell Lung Cancer: A Systematic Review and Meta-Analysis. (18th August 2020) - Wang, Yi; Wang, Yan; Li, Jialong; Li, Jue; Che, Guowei
Abstract : Aim . To explore the clinicopathological and prognostic role of PIK3CA gene mutation and expression in non-small-cell lung cancer (NSCLC) patients. Methods . A systematic and comprehensive literature search was conducted through EMBASE (via OVID), Web of Science, and PubMed. Relative risks (RRs) and hazard ratios (HRs) with 95% confidence intervals (CIs) were combined to evaluate the relationship of the PIK3CA gene with clinicopathological parameters and the survival of NSCLC patients, respectively. Results . A total of 13 studies involving 3908 patients were analyzed in our study. Only lymph node metastasis status had an association with PIK3CA mutation (RR = 2.823 ; 95% CI: 1.128-7.065; P = 0.029 ). The results indicated that PICK3CA mutation was related with overall survival (OS) (HR = 1.55 ; 95% CI: 1.13-2.13; P = 0.007 ), progression-free survival (PFS) (HR = 1.48 ; 95% CI: 1.06-2.08; P = 0.023 ), and cancer-specific survival (CSS) (HR = 2.63 ; 95% CI: 1.00-6.92; P = 0.005 ). Furthermore, PIK3CA high expression was more prevalent in NSCLC patients with smoking history (RR = 2.42 ; 95% CI: 1.04-5.61; P = 0.040 ). However, no significant relation between PIK3CA expression and OS was found (HR = 0.80 ; 95% CI: 0.58-1.12; P = 0.193 ). Conclusion . PIK3CA mutation may affect lymph node metastasis and serve as a promising prognostic factor, and smoking may be related with PIK3CA high expression in NSCLC patients. However, more well-designed prospective researches are needed to verify the abovementioned findings.